Study the effect of agar extraction pH on its yield and physical properties from the Syrian marine alga Pterocladia capillacea (Latakia University Journal -Basic Sciences Series, 2019)
The research aims to study is to study the effect of the pH factor of Pterocladia capillacea on agar yield and some of its physical properties using different degrees of pH (4- 5.5 - 5.5 - 6.5 - 7.5 - 7.5 - 8). The maximum yield of agar was 37.45% at pH = 5 and 562g / cm2 and viscosity 10.7cP and 15.45% at pH = 8 with the highest strength of 768 g /cm2 and viscosity of cP 156. The degree of melting and melting of agar Between (22- 33.5 οC) and (75- 86 οC), respectively.